Net effects of conservation agriculture principles on sustainable land use: A synthesis - Liangang Xiao; Nikolaus J. Kuhn; Rongqin Zhao; Lianhai Cao (Global Change Biology, 2021)
Despite the strong recommendations from scientists, to till or not to till remains a confusing question for many farmers around the world due to the worries of crop yield decline and negative impacts on soils and environment. A confused understanding of the role of the individual principles of conservation agriculture significantly limits the effectiveness and applicability of soil conservation strategies and frameworks to achieve sustainable agriculture. By distinguishing clearly between the different principles of conservation agriculture, the net effects of no‐tillage on improving and sustaining agro‐ecosystems are analyzed based on 49 recent meta‐analyses in this study. The review shows that no‐tillage leads to a significant decline of crop yield (−8.0% to 10.0%, median: −1.9%), whereas residue retention represents the key driver for improving crop production (4.0%–28.0%, median: 8.2%). The efficacy of no‐tillage for water erosion control, especially runoff (−24.0% to −0.7%, median: −10.0%), is often insignificant and otherwise lower compared to residue retention (−87.0% to −14.0%, median: −45.5%). Soil carbon sequestration potential under conservation tillage is quite limited or even close to zero, and if any, it can likely be attributed to the associated residue retention (−0.1% to 12.8%, median: 9.7%) rather than no‐tillage (−2.0% to 10.0%, median: 4.8%). Our analysis illustrates that in conservation agriculture, no‐tillage as the original and central principle of soil management is often less effective than associated supplementary measures, in particular residue retention. Residue retention may therefore play a key role for achieving sustainable land use. An additional benefit of residue retention is the less dramatic change of farming practices compared to no‐tillage. The results of this review illustrate that a new framework for assessing the benefits of conservation practices has to be developed. To till, or not to till, is not the question: residue retention seems more critical.